A representação da mulher na publicidade: um estudo linguístico-discursivo de anúncios de eletrodomésticos das décadas de 50 e 90 - Santicioli, Bruna Giacomeli Maia (2014)
The objective of this research is analyze the representation of woman in appliances ads from the 50s and 90s, that were published in the newspaper O Estado de S. Paulo in order to identify through linguistic-discursive strategies, the socially constructed image of women comparing the figure of the woman in different ads and periods. In order to achieve our purpose, we selected the corpus of this research with ten published in the newspaper O Estado de S. Paulo ads and we base the dissertation studies of discourse analysis, in connection to the researches focused on advertising language and related historical and social aspects the woman figure. In this search, we found that the ads in appliances in the 50s had, either through linguistic elements or through visual elements or a combination of both, the image of woman as housewife, responsible for doing housework with tenacity and joy and use or aspire to have the appliances announced. In the 90s, the focus is on appliance features and often, the prices, not the consumer potential. However, although it is clear, more veiled way, the association of women to appliances, which indicates that it remains the priority user of these devices or who infer that the ads should be